ANALISIS KEBIJAKAN PERATURAN MENTERI AGAMA RI NOMOR 19 TAHUN 2020 : IMPLIKASI TERHADAP PENINGKATAN KOMPETENSI GURU MADRASAH (Studi Kasus di MTsN 1 Bandung) - Dahlan, Elon; Wasliman, Iim; Andriana Gaffar, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the implications of the Indonesian Minister of Religious Affairs Regulation No. 19 of 2020 on improving the competency of madrasah teachers, with a case study at MTsN 1 Bandung. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that the planning process was well- structured but lacked comprehensive involvement from all school components. Organizational efforts were evident, yet coordination challenges remained. Implementation of the regulation highlighted the active managerial role of the principal but faced obstacles in vision alignment and teacher motivation. Supervision was evaluative rather than formative, occurring only once per year, limiting feedback opportunities for teachers. This study concludes that continuous professional development, improved supervision frequency, and inclusive planning are necessary to optimize policy implementation. These findings contribute to enhancing religious education quality in Indonesia. Keywords: Teacher competency, policy analysis, madrasah education, qualitative research, education management.